Zinc uptake, utilization and their expression in upland rice - Shariifanpour, Golnaz (2015)
Zinc deficiency is one of the most common micronutrient disorders in rice, for both lowland varieties grown under flooded conditions and upland varieties under upland condition. The concentration of Zn in acidic soil is very low; as soils of Malaysia are acidic so Zn monitoring in Malaysia is vital. Owing to the important role of Zn element in human health and wellness, and on the other hand, lack of Zn causes much serious illness, monitoring Zn in upland rice, as a nutrient factor is essential. In addition, the industry has to identify and breed for nutrient efficient varieties. Zinc is one of the important elements of protein transport in plants so it is vital to identify zinc as a main plant protein transporter. The main goal of this project was to evaluate Zn uptake and metabolism in upland rice, in order to formulate correct fertilizer recommendations. Zn-efficient upland rice was identified in the first study where the effect of different Zn concentration on root characteristics of 7 upland rice landraces were evaluated. To increase Zn content in rice in order to supply adequate Zn in Malaysian diet, the effect of different compost and different sources of Zn on two upland rice landraces identified from study 1 was evaluated in a glasshouse study. The expression of OsZIP1, OsZIP3, OsZIP4, OsZIP5 and OsZIP8 involved in Zn uptake by the two selected upland rice genotypes in the leaves and roots were also elucidated. Results revealed that, soluble forms of Zn are readily available to plants and the uptake of Zn is linear with concentration in the nutrient solution. In addition,, plants grown in solution treated with Zn accumulate a great proportion of this metal in the roots. Other root parameters (length, average diameter, surface area, volume, and number of root) did not show any significant differences in 0 to 20 mg Zn L-1, but they decreased significantly at 30 mg Zn L-1. This shows that Zn in high concentration causes root growth disorder. At 30 mg Zn L-1 young plants died, possibly due to toxic effect of Zn. All root parameters increased significantly during four weeks of observation. Bertih variety had the most Zn uptake (0.0328 mg plant-1) and Nabawan had the lowest Zn uptake (0.0138 mg plant-1) during the four weeks. It seems that the Zn content of plants varies considerably, reflecting different factors affecting the Zn uptake by the landraces tested. All types of composts showed positive effects on Zn concentrations and uptake in all parts of rice. Vermicompost is the most effective compost among these three composts. It has been found that although chicken compost has more Zn concentration, it seems that because of high concentration of other elements (such as P which have interactions with Zn), plant could not absorb Zn properly. On the other hand, because of high N in chicken compost, and increasing the dry weight of plant under this treatment, Zn uptake did not show a significant difference with Zn uptake in plants grown in vermicompost treatment. Application of Zn-amended organic composts increased the percentage distribution of Zn in grain more than the application of ZnSO4 or Zn-EDTA alone. In addition,, the results of analysis of the best soil treatment (Vermicompost+ZnSO4) compared to control for Zn content in different fractions showed application of vermicompost caused a significant increase in the content of water soluble plus exchangeable, organic complexed fraction of soil Zn. Results of molecular study in roots and shoot showed an over expression of OsZIP4, OsZIP1, OsZIP8, OsZIP5 under Zn deficient conditions , but not OsZIP3 (OsZIP3 is not expressed in roots and shoots). Generally, it can be concluded that rice variety detected with high Zn uptake could offer a sustainable and cost-effective way to overcome Zn deficiency problems and uptake of Zn by all parts of rice illustrated an increase in the presence of vermicompost+inorganic Zn sources (ZnSO4 and Zn-EDTA) which was the most effective method for Zn fortification in rice plants. Also, application of organic matter under upland condition influenced favourably the transformation of applied Zn in soil fractions which are available to the nutrition of rice plants. From molecular aspect, as OsZIPs are Zn transporter that functions in Zn uptake and distribution; Zinc homeostasis is important to the proper growth and development of rice.